Efektivitas Pembelajaran Daring Program Studi Pendidikan Matematika Universitas Negeri Gorontalo - Agus Humalanggi; Sumarno Ismail; Yamin Ismail; Dewi Rahmawati Isa (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This article discusses the effectiveness of online learning in the mathematics education study program at the State University of Gorontalo. It intends to describe the effectiveness of online learning in the mathematics education study program. This research uses descriptive quantitative research methods and data collection techniques by distributing questionnaires and observations. The results showed that the effectiveness of online learning in the mathematics education study program at the State University of Gorontalo was effective. The effectiveness is indicated by the results of observations that meet the effectiveness criteria. The analysis of the questionnaire obtained based on three aspects is in the fairly good category, namely the learning planning aspect with a percentage of 76.67% classified in the good enough category, and the online learning activity aspect with a percentage of 73.11% is classified in the good enough category, aspects of media and online learning facilities with a percentage of 64.83% classified in the fairly good category. This result means that online learning can be an effective learning alternative if it has a good learning plan, interesting learning activities, as well as supporting and adequate media and facilities.